2018
DOI: 10.1007/s10388-018-0620-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an elemental diet on oral mucositis of esophageal cancer patients treated with DCF chemotherapy: a multi-center prospective feasibility study (EPOC study)

Abstract: PurposeOral mucositis (OM) is one of the most uncomfortable adverse events experienced by cancer patients undergoing chemotherapy. Previous reports have revealed that the oral administration of an elemental diet (ED) may prevent OM. However, the incidence of OM has not been accurately determined by specialized diagnostic methods and the effects of an ED on OM remain unclear. We investigated the dose that could feasibly be administered and its effects with regard to the suppression of OM in esophageal cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
1
27
0
2
Order By: Relevance
“…Further details about the literature search process are provided in Figure 1. Relevant studies were identified [52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68], and their results are summarized in Table 2 and Table 3.…”
Section: Review On the Use Of Oligomeric Enteral Nutrition Formulamentioning
confidence: 99%
See 4 more Smart Citations
“…Further details about the literature search process are provided in Figure 1. Relevant studies were identified [52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68], and their results are summarized in Table 2 and Table 3.…”
Section: Review On the Use Of Oligomeric Enteral Nutrition Formulamentioning
confidence: 99%
“…Regarding chemotherapy-induced intestinal mucositis [60,61,62,63,64,65,66,67,68] (Table 3), all the studies we have found used the same oligomeric formula of enteral nutrition (Elental ® ). In total there are 345 patients, of whom 203 were treated with this oligomeric enteral nutrition, and the rest are controls without enteral nutrition.…”
Section: Review On the Use Of Oligomeric Enteral Nutrition Formulamentioning
confidence: 99%
See 3 more Smart Citations